Relationship between physical fitness and the physical demands of 50-over cricket in fast bowlers - Webster, T. M.; Comfort, P.; Jones, P. A. (The Journal of Strength and Conditioning Research, 2022)
Professional cricket is constantly evolving and resulting in increased physiological demand placed on players. Fast bowlers experience the greatest physical demand during match-play; despite this, research has overlooked the importance of specific physical attributes to optimizing physical match performance. The aim of this study was to investigate the relationships between 50-Over physical match performance and tests of physical qualities in fast bowlers. Fifteen professional male fast bowlers (age = 23.8 ± 4.0 years; height = 183.4 ± 6.7 cm; body mass = 82.9 ± 9.2 kg) participated in the study. Subjects completed the following physical fitness tests; sum of skinfolds, countermovement jump (CMJ), 20-m sprint, and the Yo-Yo intermittent recovery test level 1. Global positioning system data were collected during 6 professional 50-Over fixtures. Moderate correlations were established between CMJ height to total distance covered (r = 0.585; p = 0.022), sprinting distance (Rho = 0.554; p = 0.032), and maximal velocity (r = 0.567; p = 0.027); 20-m sprint time to total distance covered (Rho = -0.519; p = 0.047) and PlayerLoad (Rho = -0.561; p = 0.03); and Yo-Yo distance to total match distance (r = 0.520; p = 0.047) and sprinting distance (Rho = 0.524; p = 0.045). These findings demonstrate the predictive importance of prolonged intermittent running ability, jump, and sprint performance to match running performance of elite fast bowlers in 1-day cricket. Strength and conditioning coaches should use such information to design training to ensure fast bowlers are adequately conditioned to meet the demands of match running performance.